Some Reflections on the Relation Between Finance and Distribution in the 1980s - Kregel, J. A. (Journal of Income Distribution®, 1992)
Growth and technological change have created difficulties in linking changes in individual and functional distribution. The problem is complicated by changes in financial structure in the 1980s; making it more difficult to trace the effect on distribution of such events is the increase in government indebtedness, high interest rate policy, or the collapse of savings and loan banks. This paper tries to outline these difficulties and is a first step in assessing how these factors affect individual distribution.